Pelatihan Hidroponik Sistem NFT bagi Kelompok Pertanian Patuh Angen di Kota Mataram - Primawati, Sri Nopita; Nissa, Ita Chairun; Nufida, Baiq Asma; Rizka, Muhammad Arief; Febrilia, Baiq Rika Ayu; Sukri, Akhmad (Jurnal Pengabdian UNDIKMA, 2021)
This community service activity aims to increase the knowledge and competence of the Patuh Angen agricultural group through NFT hydroponic training. This training was applied to the Patuh Angen’s Farming Group located in the South Marong Jamaq neighborhood, Karang Baru Village, Selaparang District, Mataram City. The training was carried out using agricultural extension methods and agricultural process assistance methods starting from socializing the objectives, explaining the material, monitoring the planting process, harvesting plants, to reflecting on all the processes carried out. The results of this community service activity show that the agricultural group is able to practice NFT hydroponics and produce vegetables with good quality.